A 22‐single nucleotide polymorphism Alzheimer's disease risk score correlates with family history, onset age, and cerebrospinal fluid Aβ42. Issue 12 (15th June 2015) - Sleegers, Kristel; Bettens, Karolien; De Roeck, Arne; Van Cauwenberghe, Caroline; Cuyvers, Elise; Verheijen, Jan; Struyfs, Hanne; Van Dongen, Jasper; Vermeulen, Steven; Engelborghs, Sebastiaan; Vandenbulcke, Mathieu; Vandenberghe, Rik; et al.
Abstract: Introduction: The ability to identify individuals at increased genetic risk for Alzheimer's disease (AD) may streamline biomarker and drug trials and aid clinical and personal decision making. Methods: We evaluated the discriminative ability of a genetic risk score (GRS) covering 22 published genetic risk loci for AD in 1162 Flanders‐Belgian AD patients and 1019 controls and assessed correlations with family history, onset age, and cerebrospinal fluid (CSF) biomarkers (Aβ1–42, T‐Tau, P‐Tau181P ). Results: A GRS including all single nucleotide polymorphisms (SNPs) and age‐specific APOE ε4 weights reached area under the curve (AUC) 0.70, which increased to AUC 0.78 for patients with familial predisposition. Risk of AD increased with GRS (odds ratio, 2.32 (95% confidence interval 2.08–2.58 per unit; P  < 1.0e −15 ). Onset age and CSF Aβ1–42 decreased with increasing GRS ( P onset_age  = 9.0e −11 ; P Aβ  = 8.9e −7 ). Discussion: The discriminative ability of this 22‐SNP GRS is still limited, but these data illustrate that incorporation of age‐specific weights improves discriminative ability. GRS‐phenotype correlations highlight the feasibility of identifying individuals at highest susceptibility.